AMIN AL-KHULI: RÂID TAJDÎD AL-BALÂGHAH FÎ AL-ASHR AL-HADÎTS - Muttaqin, Mohammad Izdiyan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This research aims to uncover the names of thinkers who encourage the renewal of Balaghah (Arabic Islamic Rethoric), as well as to find the pioneer of the renewal of Balaghah in modern era. This research is a descriptive qualitative research. The author takes data from Munir Muhammad Kholil Nida's dissertation (1980), and other references related to the title of the discussion. Among the results of this study, it is known that Munir mentioned important names who are considered the pioneers of Balaghah reform in modern times, including: Ahmad Badawi, Mustafa Amin and Ali Jarim, Abdul Aziz Basyari, Anis Al-Maqdisi, Ali Al-Umari, Abdu Ar-Razaq Muhyiddin, Amin Al-Khuli, and Ahmad As-Syaib. And the most important pioneers of reform among them were Amin Al-Khuli and Ahmad As-Syaib. Because both of them made a special book on the principles of their renewal ideas. And Amin Al-Khuli is considered superior to Ahmad As-Syaib with a logical division of titles, and the ability to provide satisfactory explanations in the selection of titles in the new Balaghah concept.